Dual‐Silica Template‐Mediated Synthesis of Nitrogen‐Doped Mesoporous Carbon Nanotubes for Supercapacitor Applications. Issue 12 (30th December 2022) - Zhang, Qian; Deng, Chao; Huang, Zaimei; Zhang, Qingcheng; Chai, Xiaocheng; Yi, Deliang; Fang, Yuanyuan; Wu, Minying; Wang, Xingdong; Tang, Yi; Wang, Yajun
Abstract: 1D carbon nanotubes have been widely applied in many fields, such as catalysis, sensing and energy storage. However, the long tunnel‐like pores and relatively low specific surface area of carbon nanotubes often restrict their performance in certain applications. Herein, a dual‐silica template‐mediated method to prepare nitrogen‐doped mesoporous carbon nanotubes (NMCTs) through co‐depositing polydopamine (both carbon and nitrogen precursors) and silica nanoparticles (the porogen for mesopore formation) on a silica nanowire template is proposed. The obtained NMCTs have a hierarchical pore structure of large open mesopores and tubular macropores, a high specific surface area (1037 m 2 g −1 ), and homogeneous nitrogen doping. The NMCT‐45 (prepared at an interval time of 45 min) shows excellent performance in supercapacitor applications with a high capacitance (373.6 F g −1 at 1.0 A g− 1 ), excellent rate capability, high energy density (11.6 W h kg −1 at a power density of 313 W kg −1 ), and outstanding cycling stability (98.2% capacity retention after 10 000 cycles at 10 A g −1 ). Owing to the unique tubular morphology, hierarchical porosity and homogeneous N‐doping, the NMCT also has tremendous potential in electrochemical catalysis and sensing applications. Abstract : This work presents a dual‐silica template‐mediated strategy to prepare nitrogen‐doped mesoporous carbon nanotubes (NMCT). The obtained NMCT has a hierarchical pore structure and homogeneous nitrogen doping. The structural feature brings excellent performance in supercapacitor applications with a high capacitance, excellent rate capability, and outstanding cycling stability. The NMCT also has tremendous potential in electrochemical catalysis and sensing applications.